Kyselina nikotinová v prevenci ischemické choroby srdeční - Digby, Janet E; Lee, Justin M. S; Choudhury, Robin P (Current Opinion in Lipidology, 2010)
Nicotinic acid is the most potent treatment clinically available for lowering LDL cholesterol and VLDL cholesterol and raising HDL cholesterol. The strong inverse relationship between coronary heart disease risk and HDL cholesterol at all levels of LDL cholesterol has, therefore, given renewed emphasis on the therapeutic potential of niacin. The purpose of this review is to evaluate advances in the elucidation of mechanisms by which nicotinic acid affects the lipoprotein profile and, more recently, emerging evidence of nonlipid-mediated anti-inflammatory effects. RECENT FINDINGS: Niacin treatment reduces cardiovascular events and the progression of atherosclerosis. Identification of G-protein-coupled receptor 109A as the receptor for nicotinic acid has provided insights into how treatment with this compound leads to a favourable alteration in HDL cholesterol. In addition, evidence of nonlipid-mediated anti-inflammatory effects of nicotinic acid such as direct enhancement of adiponectin secretion demonstrates a novel atheroprotective role. SUMMARY: Whether nicotinic acid use becomes routine in the treatment of atherosclerosis is likely to be determined by the results of two ongoing clinical outcome trials. In addition, further research is required to explore the 'pleiotropic' effects of nicotinic acid and will ultimately provide a platform for the development of newer molecules that are potentially beneficial but without the well known side-effects.
Keywords: niacin; financování organizované; klinické zkoušky jako téma; Financing, Organized; Humans; Clinical Trials as Topic; lidé; nemoci koronárních tepen; LDL-cholesterol; Niacin; Cholesterol, LDL; HDL-cholesterol; Coronary Artery Disease; Cholesterol, HDL